The Brasília experiment: The heterogeneous impact of road access on spatial development in Brazil. (March 2020) - Bird, Julia; Straub, Stéphane
Highlights: Studies the impact of the expansion of the road network on municipal population and economic activity between 1970 and 2000. Addresses endogeneity in road location using as natural experiment the creation of the capital city Brasilia in 1960. Identification strategy combines inconsequential unit approach and use of planned routes as instruments. Improvement in access to State capitals generated agglomeration effects in terms of population and GDP growth. Effects were stronger up to 200 km around cities and for areas with good amenities and a high share of non-agricultural GDP. Abstract: This paper studies the impact of the rapid expansion of the Brazilian road network, which occurred from the 1960s to the 2000s, on the growth and spatial allocation of population and economic activity across the country's municipalities. It addresses the problem of endogeneity in infrastructure location by using an original empirical strategy, based on the historical natural experiment constituted by the creation of the new federal capital city Brasília in 1960. It highlights long term center-periphery agglomeration effects and shows heterogeneous effects of roads depending on the characteristics of metropoles they lead to and on the location of the municipalities themselves, in line with predictions in terms of agglomeration economies.